Comparative Analysis of Different Anodic Inoculum in Microbial Fuel Cell for Efficient Methylene Blue Dye Degradation - Ailin Baiju; M. Swathi; Anupama Chacko; U. Akhila; Sinoy Johnson; M. S. Jestin; P. Priyaja; P. P. Rajesh; Md Tabish Noori (Current Microbiology, 2026)

Marker-based standardisation and in-vitro biological activity evaluation of Sudarshanam tablet – an important ayurvedic formulation - Veena K Namboodiri; Tom Cherian; Anitha R; Swathi M; Suresh V Nampoothiri (Natural Product Research, 2026)

Elucidating the molecular basis of Streptomyces antifungal activity against Fusarium verticillioides, causing maize ear and stalk rot pathogen - K.N. Pallavi; M.K. PrasannaKumar; J. Harish; R. Karan; Gopal Venkateshbabu; M. Nithish; C. Manjunatha; Deepaka; Swathi S. Patil; Aditya Narayan Sarangi (Biocatalysis and Agricultural Biotechnology, 2026)

Enterobacter cloacae: a newly identified soft rot pathogen of radish with cross-species pathogenicity - Chandrashekar Byalahalli Subramani; M. K. Prasannakumar; Aditya Kukreti; Manjunatha Channappa; Pramesh Devanna; Karan R; Swathi S. Patil; Harish J; Shreedevasena S; Sateesh Kagale (World Journal of Microbiology and Biotechnology, 2026)

Isolation and Anti-Cancer Activity of Vinblastine from Colletotrichum siamense, an Endophyte of Catharanthus roseus (L.) G. Don - Eranna Swathi; Vineetha Mavinamane Shrikanth; Mohammed A. Alshamrani; Bassam S. M. Al Kazman; Omaish S. Alqahtani; Farkad Bantun; Mater H. Mahnashi; Nayef Abdulaziz Aldabaan; Ibrahim Ahmed Shaikh; Basheerahmed Abdulaziz Mannasaheb; Aejaz Abdullatif Khan; Sunil S. More (Journal of Pharmaceutical Innovation, 2025)

Correction to: Effectiveness of a negative ion generator “instashield” for indoor air disinfection: evidence from tertiary care hospital and GLP laboratory settings - Neema Kumari; Vikas Sahu; Kavya Chintala; Swathi C. M.; Chandra Sri Durga; Hima Bindu Mantravadi; Palavardhan Peddapalegani; Kranti Kiran Reddy Ealla (Bulletin of Atmospheric Science and Technology, 2025)

Effectiveness of a negative ion generator “Instashield” for indoor air disinfection: evidence from tertiary care hospital and GLP laboratory settings - Neema Kumari; Vikas Sahu; Kavya Chintala; Swathi C. M.; Chandra Sri Durga; Hima Bindu Mantravadi; Palavardhan Peddapalegani; Kranti Kiran Reddy Ealla (Bulletin of Atmospheric Science and Technology, 2025)

Topical Wound Healing Effects of Bauhinia Purpurea and Ficus Carica Extracts Compared to Povidone-Iodine in Sprague Dawley Rats - M. Shilpa; Jamal Moideen Muthu Mohamed; Yahya I. Asiri; Krishnaraju Venkatesan; Swathi Gurajala; Pooja Muralidharan; Gamal Osman Elhassan; Hassabelrasoul Elfadil; Rehab Ahmed; Nizar Sirag; Premalatha Paulsamy (Journal of Pharmaceutical Innovation, 2025)

The role of atmospheric and oceanic factors on the record low Antarctic sea ice extent of 2023 - M. Swathi; Avinash Kumar; Juhi Yadav; Rahul Mohan (Global and Planetary Change, 2025)

Trends in Antarctic Sea Ice and Albedo: Impacts of Ocean‐Atmospheric Processes - M Swathi; Aakriti Srivastava; Avinash Kumar; Juhi Yadav; Dinesh Chandra Gupta; Rahul Mohan (International Journal of Climatology, 2025)
Surface albedo (SAL), a critical factor in climate studies, significantly impacts the Earth's radiation budget and sea ice dynamics. The long‐term spatial and temporal variability of Antarctic SAL were derived from the third edition of the Cloud, Albedo, and Surface Radiation Dataset (CLARA‐A3). The analysis focused on spring and summer across five longitudinal sectors around Antarctica. The relationships of sea ice concentration (SIC) and SAL with climatic variables such as sea surface temperature (SST), 2 m air temperature (T2m), turbulent heat flux, and total cloud cover are explored in detail. The study examined SAL changes in two distinct timescales, pre‐2015 (1979–2015) and post‐2015 (2016–2021), to understand sea ice variations and trends in Antarctic climate change. The study revealed contrasting summer SAL trends, with a positive trend pre‐2015 and a decreasing trend post‐2016 across most of Antarctica, except the Amundsen‐Bellingshausen Sea, which showed an opposite trend. West Antarctica exhibited higher SAL compared to East Antarctica. SAL and SIC were significantly negatively correlated with SST, T2m, and turbulent heat flux across all sectors. Cross‐seasonal lead–lag analysis indicated that increased turbulent heat flux was followed by an increase in SAL after 1–5 months. Wind patterns showed that winds from higher to lower latitudes increased SIC and SAL, while winds from lower to higher latitudes reduced SIC. Post‐2015, notable wind direction reversals were observed in the Antarctic Peninsula during spring. Sectors with higher cloud cover absorbed more ocean heat, reducing turbulent heat flux and affecting SAL. Overall, post‐2015 observations highlighted major shifts in sea ice dynamics and SAL trends during both spring and summer seasons. The SIC decreased markedly across all sectors, with the Weddell Sea showing the most significant reduction. This study highlights regional and seasonal variations in SAL and its interactions with SIC and climatic factors, emphasising shifts in trends post‐2015.

Gender specific SNP markers in Coscinium fenestratum (Gaertn.) Colebr. for resource augmentation - Remya Unnikrishnan; Swathi Balakrishnan; M Sumod; P Sujanapal; Bipin Balan; Suma Arun Dev (Molecular Biology Reports, 2024)

A review of the physiological effects of microgravity and innovative formulation for space travelers - Jey Kumar Pachiyappan; Manali Patel; Parikshit Roychowdhury; Imrankhan Nizam; Raagul Seenivasan; Swathi Sudhakar; M. R. Jeyaprakash; Veera Venkata Satyanarayana Reddy Karri; Jayakumar Venkatesan; Priti Mehta; Sudhakar kothandan; Indhumathi Thirugnanasambandham; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)

Emerging and Changing Patterns in Prevalence of Anti-leptospiral Antibodies Against Different Serogroups in Livestock in Andaman-Islands Ecosystem - K. Vinod Kumar; M. Swathi; Prajakta P. Bokade; V. Bharath; S. SowjanyaKumari; Jai Sunder; D. Hemadri; B. R. Shome; V. Balamurugan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Synthesis, Characterization, Investigation of DNA Interactions and Biological Evaluation of Co(II), Ni(II), Cu(II) and Zn(II) Complexes with Newly Synthesized 2-methoxy 5-trifluoromethyl benzenamine Schiff Base - M. Swathi; Dasari Ayodhya; Shivaraj (Journal of Fluorescence, 2024)

Mapping serogroup distribution and seroprevalence of leptospirosis in livestock of Assam, Northeastern State of India: Unveiling uncommon Leptospira serogroups - K. Vinod Kumar; Swathi M; Prajakta P. Bokade; Sowjanyakumari S; Bharath V; G. Govindaraj; Divakar Hemadri; B.R. Shome; V. Balamurugan (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Spatiotemporal evolution of sea ice and its teleconnections with large-scale climate indices over Antarctica - M. Swathi; Avinash Kumar; Rahul Mohan (Marine Pollution Bulletin, 2023)

Detection of the occurrence of the fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) strains on maize in Southern Rajasthan India - S. Ramesh Babu; P. Perumal; Sonika Joshi; Raja Manoharan; Deepika Kalyan; Swathi Penuballi; R. K. Kalyan; M. K. Mahla; Pramod Rokadia; Beerendra Singh (Journal of Plant Diseases and Protection, 2022)

Protective Effect of Lactobacillus sporogenes against Arsenic-Induced Hematological Alterations in Male Albino Wistar Rats - Swathi Bora; M. Lakshman; D. Madhuri; B. Kalakumar; M. Udayakumar (Biological Trace Element Research, 2022)

A comprehensive insight on the biological potential of embelin and its derivatives - N. Jeelan Basha; S. M. Basavarajaiah; Swathi Baskaran; Prasanna Kumar (Natural Product Research, 2022)

Seismic velocity imaging of the Kumaon–Garhwal Himalaya, India - Prantik Mandal; D. Srinagesh; R. Vijayaraghavan; G. Suresh; B. Naresh; P. Solomon Raju; Aarti Devi; K. Swathi; Dhiraj K. Singh; D. Srinivas; Satish Saha; M. Shekar; et al. (Natural Hazards, 2022)

Characterization of earthquake hazard at the Palghar and Pulichintala swarm activity regions (India) through three-dimensional modelling of b-value and fractal (correlation) dimensions - Prantik Mandal; D. Srinagesh; G. Suresh; B. Naresh; Mahalaxmi Naidu; Dhiraj Kumar Singh; K. Swathi; Arti Devi; S. Vittal; P. K. Vengala; R. Vijaya Raghavan; M. Shekar; et al. (Natural Hazards, 2021)

Flow cytometry analysis of apoptotic progression and expression analysis of four apoptosis-related genes in Penaeus vannamei in response to white spot syndrome virus infection - A. Swathi; M. S. Shekhar; Vinaya Kumar Katneni; K. K. Vijayan (VirusDisease, 2021)

Morphological and molecular characterization of new plant type core set for yield and culm strength traits in rice (Oryza sativa L.) - Rachana Bagudam; K. B. Eswari; Jyothi Badri; G. Lakshmi Devi; L. R. K. JaiVidhya; P. Bhavani; Gattu Swathi; M. Bharath; P. Raghuveer Rao; Jukanti Aravind Kumar; R. Abdul Fiyaz; C. N. Neeraja; et al. (Journal of Plant Biochemistry and Biotechnology, 2021)

Iron limitation study in the North Indian Ocean using model simulations - M K Sharada; C Kalyani Devasena; P S Swathi (Journal of Earth System Science, 2020)

Remote influences on the Indian monsoon low-level jet intraseasonal variations - M. S. Swathi; Takeshi Izumo; Matthieu Lengaigne; Jérôme Vialard; M. R. Ramesh Kumar (Climate Dynamics, 2020)

Functional neuroanatomy of the human eye movement network: a review and atlas - Benjamin Coiner; Hong Pan; Monica L. Bennett; Yelena G. Bodien; Swathi Iyer; Therese M. O’Neil-Pirozzi; Lorene Leung; Joseph T. Giacino; Emily Stern (Brain Structure and Function, 2019)

Are Tanycytes the Missing Link Between Type 2 Diabetes and Alzheimer’s Disease? - Sudhanshu P. Raikwar; Sachin M. Bhagavan; Swathi Beladakere Ramaswamy; Ramasamy Thangavel; Iuliia Dubova; Govindhasamy Pushpavathi Selvakumar; Mohammad Ejaz Ahmed; Duraisamy Kempuraj; Smita Zaheer; Shankar Iyer; Asgar Zaheer (Molecular Neurobiology, 2019)

Genome size estimation of brackishwater fishes and penaeid shrimps by flow cytometry - A. Swathi; M. S. Shekhar; Vinaya Kumar Katneni; K. K. Vijayan (Molecular Biology Reports, 2018)

Novel SAHA analogues inhibit HDACs, induce apoptosis and modulate the expression of microRNAs in hepatocellular carcinoma - Chatla Srinivas; V. Swathi; C. Priyanka; T. Anjana Devi; B. V. Subba Reddy; M. Janaki Ramaiah; Utpal Bhadra; Manika Pal Bhadra (Apoptosis, 2016)

Planning adaptation to climate change in fast-warming marine regions with seafood-dependent coastal communities - Alistair J. Hobday; Kevern Cochrane; Nicola Downey-Breedt; James Howard; Shankar Aswani; Val Byfield; Greg Duggan; Elethu Duna; Leo X. C. Dutra; Stewart D. Frusher; Elizabeth A. Fulton; Louise Gammage; et al. (Reviews in Fish Biology and Fisheries, 2016)

Phylogenetic diversity of Mesorhizobium in chickpea - Dong Hyun Kim; Mayank Kaashyap; Abhishek Rathore; Roma R Das; Swathi Parupalli; Hari D Upadhyaya; S Gopalakrishnan; Pooran M Gaur; Sarvjeet Singh; Jagmeet Kaur; Mohammad Yasin; Rajeev K Varshney (Journal of Biosciences, 2014)

Effects of LPS on P2X3 receptors of trigeminal sensory neurons and macrophages from mice expressing the R192Q Cacna1a gene mutation of familial hemiplegic migraine-1 - Alessia Franceschini; Swathi K. Hullugundi; Arn M. J. M. van den Maagdenberg; Andrea Nistri; Elsa Fabbretti (Purinergic Signalling, 2013)

Role of biology in the air-sea carbon flux in the Bay of Bengal and Arabian Sea - M. K. Sharada; P. S. Swathi; K. S. Yajnik; C. Kalyani Devasena (Journal of Earth System Science, 2008)

A coupled physical-biological-chemical model for the Indian Ocean - P. S. Swathi; M. K. Sharada; K. S. Yajnik (Journal of Earth System Science, 2000)